2023
DOI: 10.32854/agrop.v15i12.2291
|View full text |Cite
|
Sign up to set email alerts
|

Geopedological transects in karst landscapes in Campeche, Mexico

Abstract: Objective: Apples cultivated in Mexico generally are smaller and softer than those produced in other geographical latitudes considered as optimal for apple production. The aim of this evaluation was determine the effect of applications with calcium, nitrogen, potassium, magnesium, sulfur and naphthaleneacetic acid (NAA), as well as the harvest date on the quality of apple fruits. Methodology ‘Golden Smoothie’ apple trees were treated foliarly with CaCl2 with and without NAA, and with a mixture of N, K, Mg and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
7

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 0 publications
0
6
0
7
Order By: Relevance
“…The RSG of the study area resulted in a Ferric Lixisol (Cutanic, Endoloamic, Epiarenic, Humic, Profondic), differentiating from an Acrisol where the Lixisols have clay of low activity in the argic horizon and a high saturation of bases between 50-100 cm of depth, while the Acrisols, even though they also have clays of low activity in the argic horizon the base saturation is low in the depth of 50-100 cm. In this regard, no information was found reporting the presence of Luxisols in the hillside zone of La Sanana in Huimanguillo (La Chontalpa), although Zavala-Cruz et al (2016) refers to their presence in Balancán and Tenosique in the river meadow zone (Región de los Ríos), and on the other hand, Palma- López et al (2017) mention that until that year this type of soil had not been identified in Tabasco, although it was found since 2016 in regions between the municipalities of Tenosique and Balancán. The soil profile description in ejido Tecomatán, Huimanguillo, Tabasco, is shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RSG of the study area resulted in a Ferric Lixisol (Cutanic, Endoloamic, Epiarenic, Humic, Profondic), differentiating from an Acrisol where the Lixisols have clay of low activity in the argic horizon and a high saturation of bases between 50-100 cm of depth, while the Acrisols, even though they also have clays of low activity in the argic horizon the base saturation is low in the depth of 50-100 cm. In this regard, no information was found reporting the presence of Luxisols in the hillside zone of La Sanana in Huimanguillo (La Chontalpa), although Zavala-Cruz et al (2016) refers to their presence in Balancán and Tenosique in the river meadow zone (Región de los Ríos), and on the other hand, Palma- López et al (2017) mention that until that year this type of soil had not been identified in Tabasco, although it was found since 2016 in regions between the municipalities of Tenosique and Balancán. The soil profile description in ejido Tecomatán, Huimanguillo, Tabasco, is shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The study was conducted from 2020 to 2021 in the Ejido Tecominoacán, in Huimanguillo, Tabasco, inside the area of La Sabana, between coordinates 17° 55ʼ 20.43" N and 93° 36ʼ 18.787" W. The climate is warm humid with rains during the entire year Af(m) and temperatures between 26 and 28 °C annual mean, with records of total annual precipitation from 2000 to 3000 mm (Salgado-García et al, 2010;Tinal-Ortiz et al, 2020). Until a few years ago, the dominant soils in the region have been Acrisols (Palma- López et al, 2017).…”
Section: Materials and Methods Study Area And Descriptionmentioning
confidence: 99%
“…The public land has an area of 28 km 2 , and its geographical location is 18 • 20 ′ 12 ′′ N and 93 • 2 ′ 30 ′′ W. It is located in the Grijalva-Mezcalapa delta system, bordered to the north by the El Eslabón-La Tinaja-Sí Señora lakes system; to the south by the Reforma Segunda Sección public land; to the east by the Cuauhtémoc and Cruz Méndez Jalapita public lands; and to the west by the Lázaro Cárdenas public land [36]. The Úrsulo Galván public land has a warm-humid climate, abundant summer rains, precipitation between 1500 and 2000 mm, and temperatures between 24 and 26 • C. The soils correspond to the Histosol classification but also include Solonchak soil in mangrove areas [37][38][39]. The population of the Ranchería Reforma 2da Sección is 1620 people, of whom 805 are women [40].…”
Section: The Study Areamentioning
confidence: 99%
“…Forma parte de la región fisiográfica Llanura Costera del Golfo Sur, al norte y oeste presenta planicies con sedimentos aluviales del Cuaternario (Holoceno), y al sur dominan lomeríos sobre arena, limo, arenisca y conglomerado del Plioceno-Pleistoceno (SGM, 2005;Ortiz-Pérez et al, 2005). La planicie desarrolla suelos de tipo vertisol, cambisol y fluvisol de textura arcillosa a franca, fértiles y con drenaje deficiente; los lomeríos contienen Acrisols, son ácidos y pobres en nutrientes (Zavala-Cruz et al, 2014;Palma-López et al 2017a). Prevalece el clima Am (f) cálido húmedo con lluvias abundantes en verano, precipitación anual de 2400 a 2600 mm y temperatura media anual de 26 a 28 °C, al centro y norte; seguido del Af (m) cálido húmedo con lluvias todo el año, precipitación de 2600 a 2800 mm y temperatura de 24 a 26 °C, al sur (Aceves-Navarro y Rivera-Hernández, 2020).…”
Section: áRea De Estudiounclassified
“…Entre las aplicaciones del enfoque geopedológico sobresalen: a) ordenación ambiental, para el manejo de recursos naturales en el estado de Michoacán (Bocco et al, 1999), la planeación integral de usos y servicios ambientales (González et al, 2009), el análisis de geomorfología-vegetación (Michaud et al, 2013), y la evaluación de la vulnerabilidad costera ante inundaciones por el aumento del nivel del mar en Tabasco y Campeche (Ramos-Reyes et al, 2016); b) cartografía y clasificación de suelos, para explicar el efecto de las geoformas en la génesis y distribución geográfica de los suelos en los estados de Yucatán (Bautista et al, 2015), Tabasco (Zavala-Cruz et al, 2016a;Palma-López et al, 2017a) y Campeche (Palma-López et al, 2017b), y la incidencia de las geoformas en la clasificación de suelos en planicies y terrazas de Tabasco (Brindis-Santos et al 2020); y c) evaluación de tierras, para determinar el potencial forestal a nivel de cuenca (Frugoni et al, 2016), y el mapeo de clases de capacidad de uso agropecuario en el estado de Campeche (Palma-López et al, 2017b). Estos estudios generaron cartografía a nivel de paisajes geomorfológicos y relieve/modelados a escalas de reconocimiento y semidetallada.…”
Section: Introductionunclassified